Gambaran Pelaksanaan Diskusi Refleksi Kasus (DRK) Dalam Mendukung Peningkatan Pengetahuan Dan Profesionalitas Perawat - Haeril Amir; Andi Masyitha Irwan; Ariyanti Saleh (Jurnal Keperawatan Muhammadiyah, 2019)
Review Article DESCRIPTION OF THE IMPLEMENTATION REFLECTIVE CASE   DISCUSSION (DRK) IN SUPPORTING KNOWLEDGE AND NURSE PROFESSIONALITY  AbstractBackground:Reflective case discussion (DRK) is part of performance management development (PMK). The PMK component consists of standart, job description, performance indicator, monitoring system and DRK. DRK management is carried out in Hospital and health center. The development of this method must be continuously carried out as an effort to increased knowledge and professional nurses. The purpose of literature is to identify the description implementation of DRK in supporting improvement of the knowledge and professional nurse. Method: the database used in the literature making is Pubmed, Science Direct, Proquest and Wiley Online.    Result: there were 12 articles, but that met the inclusion criteria were 5 articles, result article show the benefit of DRK supporting increase knowledge and professional nurse. Discussion: the implementation of DRK a important, this method provides many benefits for nurses and has a direct impact of the health services , the development method in the future requires involvement of all parties and stakeholders support. Conclusion:the implementation of DRK in hospital useful to improve the professional of nurses, increase knowledge and confidence so it is important. Keywords: Reflective case discussion, knowledge and professional